PENGARUH BUKU CERITA BERGAMBAR BERBASIS AUGMENTED REALITY DALAM MENINGKATKAN KOSAKATA BAHASA INGGRIS ANAK USIA DINI - Dwi Septia Ochi Wahyuni; Elise Muryanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Less diverse media is still used in one of the kindergartens in the city of Padang, West Sumatra, to stimulate the English language. The aim of this study is to ascertain the influence of augmented reality picture books in assisting children to enrich their English vocabulary. This study used a quasi-experimental design. Purposive sampling technique was used to take samples. To assist in gathering data, action tests and observations are used. Statistics analysis is used for data analysis. The study's findings attest to the significant impact that augmented reality-based picture books have on increasing children’s English vocabulary.